Turbulence et determinisme. - Hillert, Mats (Edp Sciences, 1998)
The objective of this work is to offer a rather broad vision of the study and the behavior of turbulent processes. It prompts the reader to reflect about determinism. It gives the opportunity to understand matters that are at the heart of science.